A computational platform for robotized fluorescence microscopy (II): DNA damage, replication, checkpoint activation, and cell cycle progression by high‐content high‐resolution multiparameter image‐cytometry. Issue 4 (5th March 2013) - Furia, Laura; Pelicci, Pier Giuseppe; Faretta, Mario
Abstract: Dissection of complex molecular‐networks in rare cell populations is limited by current technologies that do not allow simultaneous quantification, high‐resolution localization, and statistically robust analysis of multiple parameters. We have developed a novel computational platform (Automated Microscopy for Image CytOmetry, A.M.I.CO) for quantitative image‐analysis of data from confocal or widefield robotized microscopes. We have applied this image‐cytometry technology to the study of checkpoint activation in response to spontaneous DNA damage in nontransformed mammary cells. Cell‐cycle profile and active DNA‐replication were correlated to (i) Ki67, to monitor proliferation; (ii) phosphorylated histone H2AX (γH2AX) and 53BP1, as markers of DNA‐damage response (DDR); and (iii) p53 and p21, as checkpoint‐activation markers. Our data suggest the existence of cell‐cycle modulated mechanisms involving different functions of γH2AX and 53BP1 in DDR, and of p53 and p21 in checkpoint activation and quiescence regulation during the cell‐cycle. Quantitative analysis, event selection, and physical relocalization have been then employed to correlate protein expression at the population level with interactions between molecules, measured with Proximity Ligation Analysis, with unprecedented statistical relevance. © 2012 International Society for Advancement of Cytometry